Direct building of minimal automaton for a given list - Mihov, Stoyan (Ann. Sofia Univ. Fac. Math. and Inf., 1999)
This paper presents a method for direct building of minimal acyclic finite states automaton which recongnizes a given finite list of words in lexicographical order. The size of the temporary automata which are necessary for the construction is less than the size of the resulting minimal automata plus the length of one of the longest words in the list. This property is the main advantage of our method.